Variations in physical and chemical parameters and plankton community structure in aseries of sewage-stabilization ponds - Nandini, S. (Revista de Biología Tropical, 1999)
Variations in physical and chemical parameters and plankton community structure from urban-based scwage stabilization ponds in Delhi (India) were recorded from summer lo winter months of 1992-1993. The quantified physico-chemical variables were temperature, pH, dissolved oxygen, soluble reactive phosphorus, lotal phosphorus, nitrate-nitrogen and chlorophyll-a. A qualitative analysis of the phytoplankton in all the ponds was made. Among zooplankton, rotifers, cladocerans, and copepods were identífied and quantified. Observations were taken every month concentrations of soluble reactive phosphorus, total phosphorus and nitrate-nitrogen ranged between 1.2-2.0 mg l-1, 2.0-3.5 mg l-1, and 0.075-0.30 mg l-1, respectively. Although there were no significant differences in the nutrient concentrations between any of the ponlis, the ponds receiving the raw sewage first had undetectable levels of chlorophyll-a for a greater part ofthe sampling period, As the water passedthrough the series of ponds, the quality improved and finally supported high zooplankton densities. There were summer blooms of Euglena, Pandorina, Spirulina and Oscillatoria. The commonly found rotifer species were Branchionus calyciflorus, Hexarthra mira and Filinia longiseta. Cladocera and Copepoda were represented, almost exclusively, by Moina macrocopa and Mesocyclops thermocyclopoides respectively.